Intelligenza artificiale e pubblica amministrazione in Germania. Riflessioni sui principi orientativi di carattere normativo a partire dall’esperienza tedesca - Djeffal, Christian (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2022)
This contribution, fitting into the broad context of international discussion, investigates the guiding principles of a regulatory nature for the use of artificial intelligence in the Federal Republic of Germany. Artificial intelligence (AI), which is increasingly changing our lives and our social relationships, is a research area in which the number of technologies is growing every day, being among those in development, which are regulated and guided by principles of a regulatory and strategic nature. The paper examines artificial intelligence systems in the public administration and questions what are the guidelines already in place in this field and what trends are emerging. After having reconstructed the definition of “artificial intelligence”, and after providing some examples of its application within the public administration, the contribution identifies ethics and politics as possible reference criteria for guiding principles. In the discussion, law, technology, organization, strategy and models are seen as guiding principles capable of influencing and regulating AI and describing its current trends. The paper concludes with an appeal for interdisciplinary research on the subject and for a disciplined regulation of technology in order to exploit all its positive potential.